2013
DOI: 10.1016/j.actatropica.2013.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Turning cigarette butt waste into an alternative control tool against an insecticide-resistant mosquito vector

Abstract: a b s t r a c tAnnually, 4.5 trillion cigarette butts (CBs) are flicked into our environment. Evidence exists that CB waste is deadly to aquatic life, but their lethality to the aquatic life of the main dengue vector is unknown. CBs are full of toxicants that occur naturally, during planting and manufacturing, which may act as larvicidal agents. We assessed Aedes aegypti vulnerability to Marlboro butts during its development. Overall, CBs showed insecticidal activities against larvae. At early phases of develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 20 publications
0
27
0
3
Order By: Relevance
“…However, signs of genotoxicity in house finches have been seen to increase with the amount of butt cellulose in their nests (Suarez-Rodriguez and Garcia 2014). In addition, mosquitoes that have hatched in water environments containing cigarette butts have been shown to have shorter life spans (Dieng et al 2014) and higher mortality rates during developmental stages (Dieng et al 2013). Cigarette butt leachate in seawater has also been shown to cause mortality and behavioral modifications in snails (Booth et al 2015).…”
Section: Animal Exposurementioning
confidence: 99%
“…However, signs of genotoxicity in house finches have been seen to increase with the amount of butt cellulose in their nests (Suarez-Rodriguez and Garcia 2014). In addition, mosquitoes that have hatched in water environments containing cigarette butts have been shown to have shorter life spans (Dieng et al 2014) and higher mortality rates during developmental stages (Dieng et al 2013). Cigarette butt leachate in seawater has also been shown to cause mortality and behavioral modifications in snails (Booth et al 2015).…”
Section: Animal Exposurementioning
confidence: 99%
“…Beyond being unsightly, when disposed of in the environment CBs pose a major threat to living organisms and ecosystem health (review in [ 5 ]). The few studies available report that CBs are toxic to microbes and cladocerans [ 6 ], insects [ 7 ], and also fish [ 8 ]. A recent study reported that CBs affect avian behaviour in urban ecosystems [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nicotine can be obtained from powdered tobacco leaves, extracts from tobacco plants, waste from the tobacco industry, aqueous extracts of cigarette butts, and can also be synthesized [132][133][134][135].…”
Section: Nicotinementioning
confidence: 99%
“…Dieng et al [135] studied the effect of using a pesticide solution manufactured using cigarette butts against Aedes aegypti and observed insecticidal activity against its larvae.…”
Section: Nicotinementioning
confidence: 99%